Strategic human resource management in Malaysian five star hotels: “Best practise” or environmental “fit”? - Ahmad, Rozila; Solnet, David (2010)
This paper explores the strategic human resource management (SHRM) practices in Malaysian five star hotels in an attempt to assess its relevance and to discover the most suitable human resource (HR) practices for five star hotels in developing countries. To serve this objective, it compares the HR practices used in six Malaysian five star hotels. It finds that there is considerable variation in the extent of SHRM adoption in these hotels despite the similarities of their star rating and external environment. While some hotels adopt most of the recommended HR practices in SHRM literature, some focus on matching the HR policies and practices with the environment. The occurrence of an employees’ “strike” was reported in one of the organisations with a “best practise” approach while job satisfaction and affective commitment was frequently expressed in organisations with environmental “fit”. Although this study is not sufficient to claim that some SHRM “best practise” does not have universal validity for non-managerial employees, it suggests how to improve HR practices systems for five star beach resort hotels in Malaysia and potentially in other developing countries.